THE VARIATIONS OF THE COURT JUDGMENTS: TOWARDS A COMPREHENSIVE DESCRIPTION OF THE GENRE - TARANILLA, Raquel (Comparative Legilinguistics, 2016)
This research addresses the question of whether the genre of judgment is homogeneous or whether there are any factors which determine the specific linguistic characteristics of a judgment. For this purpose, a corpus of forty Spanish judgments has been compiled (containing civil and criminal judgments, and the 1st instance and appeal instance). This paper demonstrates that both the variant of judicial order and the variant of judicial instance condition the linguistic form of judgments; therefore, we should speak about genre variation. For that reason, a compre-hensive description of the judicial genre of Spanish judgments should include such variants.